2017
DOI: 10.5539/ibr.v10n3p133
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Employee Empowerment on Employee Job Satisfaction in Five-Star Hotels in Jordan

Abstract: This paper examines the influence of empowerment on job satisfaction in five-star hotels in Jordan. The influence of empowerment on job satisfaction remains a relatively unexplored area. A 52-item questionnaire, measuring empowerment and job satisfaction, was distributed to 332 employees in 12 five-star hotels in Jordan with a 56% response rate. Principal components analysis determined the factor structure and regression analysis determined the influence of empowerment on job satisfaction. The results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
1
23
0
1
Order By: Relevance
“…The present paper suggests researchers to further examine the influence of the employee empowerment with its two types (structural and psychological) on sales &marketing workforce performance in the presence of work engagement as mediating variable. Likewise, the studies which measure structural empowerment used Hayes scales (1994) with one dimension such as (Pelitet al, 2011;Karatepe, 2013;Sattar et al, 2015;Akhtar etal., 2016;Al-Ababneh et al, 2017), while the current paper suggests that researchers could measure the structural empowerment using six dimensions (information, support, opportunities, resources, formal and informal power) as described by the Kanter's theory.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The present paper suggests researchers to further examine the influence of the employee empowerment with its two types (structural and psychological) on sales &marketing workforce performance in the presence of work engagement as mediating variable. Likewise, the studies which measure structural empowerment used Hayes scales (1994) with one dimension such as (Pelitet al, 2011;Karatepe, 2013;Sattar et al, 2015;Akhtar etal., 2016;Al-Ababneh et al, 2017), while the current paper suggests that researchers could measure the structural empowerment using six dimensions (information, support, opportunities, resources, formal and informal power) as described by the Kanter's theory.…”
Section: Resultsmentioning
confidence: 93%
“…In hotels segment, empowering front-line employees have positive influence to their satisfaction, increase the efficiency of the operations & enhance service provided as several studies have revealed (Melhem, 2004;Ayupp& Chung, 2010;Kim, 2011;Pelitet al, 2011;Al-Ababneh et al, 2017).On the contrary, Shahrilet al(2013) study did not support suggestions in which higher level of empowerment should result in higher level of job satisfaction through front-line staff in the hospitality industry, but empowerment plays a crucial role in succeeding services, guarantees and motivates the employees.…”
Section: Employee Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are many studies in the literature of tourism examining relationships between the personnel empowerment and other factors. Studies carried out in hotel enterprises show that psychological empowerment has an impact of job satisfaction (Ababneh, Sabi, Shakhsheer & Masadeh, 2017;Mohsen, 2014) organizational commitment (Işık & Yasım, 2017;Karakaş & Serçek, 2014;Kazlauskaite, Buciuniene & Turauskas, 2006;Moura, Orgambidez & Jesus, 2015), organizational identification (Yarmacı, 2012), organizational citizenship behavior (Çavuşoğlu & Güler, 2016) and cooperation among employees (Bardakoğlu & Akgündüz, 2016). There is also a lot of research about trust in supervisor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are studies that manifest the impact of trust in supervisor in hotel enterprises and conflict management methods (Toprak, Şentürk & Kılıç, 2017), intention to leave job (Pelit and Gökçe, 2019), organizational identification (Şen & Günaydın, 2019), job satisfaction (Güçer & Demirdağ, 2014) and organizational citizenship behavior (İşbaşı, 2000). According to findings of the research performed on 186 employees working at five-stars hotel enterprises in Jordan by Ababneh et al (2017), psychological empowering is an important precursor of job satisfaction. Mohsen (2014) found out in his study carried out on 528 employees in the Egypt hotel industry that "meaning" and "self-determination" dimensions of the psychological empowerment are important in terms of job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%